Rapid Improvement in Jaundice Using Transdermal Isosorbide Tape as a Nitric Oxide Donor in Two Adult Patients with Transplantation-associated Microangiopathy Related to Graft-versus-host Disease - Hiroshima, Yuki; Sato, Keijiro; Ueki, Toshimitsu; Sumi, Masahiko; Ueno, Mayumi; Ichikawa, Naoaki; Satomi, Hidetoshi; Kobayashi, Hikaru (Internal Medicine, 2022)
Two adult patients with acute leukemia developed transplantation-associated microangiopathy (TAM) related to graft-versus-host disease (GVHD). Both patients were resistant to standard therapy for TAM and GVHD, which led to markedly elevated serum total bilirubin levels of 47.5 and 10.6 mg/dL, respectively. Transdermal isosorbide tape as a nitric oxide donor was applied to Patients 1 and 2 on post-transplantation days 60 and 66, respectively, which rapidly improved their jaundice after 1 day. This is the first report to describe the efficacy of transdermal isosorbide tape for adult patients with jaundice associated with TAM related to GVHD.